2006
DOI: 10.1016/j.biomaterials.2006.01.044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental factors on the response of human corneal epithelial cells to nanoscale substrate topography

Abstract: We have previously shown that human corneal epithelial cells sense and react to nanoscale substrate topographic stimuli [Teixeira AI, Abrams GA, Bertics PJ, Murphy CJ, Nealey PF. Epithelial contact guidance on well-defined micro- and nanostructured substrates. J Cell Sci 2003;116(10):1881-92; Karuri NW, Liliensiek S, Teixeira AI, Abrams G, Campbell S, Nealey PF, et al. Biological length scale topography enhances cell-substratum adhesion of human corneal epithelial cells. J Cell Sci 2004;117(15):3153-64]. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
205
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(221 citation statements)
references
References 21 publications
12
205
1
3
Order By: Relevance
“…Although previous works suggest that filopodia can feel variations of surface topography, many contradictory results on the alignment of filopodia have been reported. 32 In light of this, our observations suggest that alignment of filopodia may be preferentially driven by nanoscale topographic features, whereas microscale patterns are necessary to permit filopodia attachment.…”
Section: Cell Mechanosensitivitymentioning
confidence: 70%
“…Although previous works suggest that filopodia can feel variations of surface topography, many contradictory results on the alignment of filopodia have been reported. 32 In light of this, our observations suggest that alignment of filopodia may be preferentially driven by nanoscale topographic features, whereas microscale patterns are necessary to permit filopodia attachment.…”
Section: Cell Mechanosensitivitymentioning
confidence: 70%
“…Yet, this general trend in some cases is dependent on cell type, material properties and culturing conditions. For example, Teixeira et al [76] demonstrated that epithelial cells cultured on narrow ridges (70 nm and 400 nm pitch) can assume a spindlelike morphology parallel or orthogonal to the pattern direction, according to the culturing conditions. The molecular mechanisms governing cell alignment are not fully characterized, although it is hypothesized that filopodial activity perpendicular to the pattern direction is decreased owing to unfavoured stress tension [77].…”
Section: Topo-cue-mediated Crosstalkmentioning
confidence: 99%
“…Microtopography influences cell adhesion, proliferation and differentiation [1,2] and, more recently, it has become clear that nanotopography also guides cell behaviour greatly [3,4]. In some applications, in which guiding the cell orientation is essential to achieve a functional tissue, such as for tendons, nerves, corneal stroma and intervertebral-disc regeneration, contact guidance of cells by micro-and nano-topographical patterns is a promising perspective [5,6]. Chemical cues in the form of various different biomolecules (nanometre scale), such as adhesive protein or growth factors, also influence cell behaviour crucially.…”
Section: Nanofeatures On Surface Biomaterialsmentioning
confidence: 99%